Assessment of indoor air pollution exposure in urban hospital microenvironments - Mohammadyan, Mahmoud; Keyvani, Sepideh; Bahrami, Ali; Yetilmezsoy, Kaan; Heibati, Behzad; Pollitt, Krystal J. Godri (SPRINGER, 2019)
Hospitals are microenvironments containing populations with potentially enhanced sensitivity to air pollution. The objectives of this study were to characterize the concentration of indoor and outdoor size-fractionated particulate matter (PM) at two urban hospital sites in Kashan, Iran, and to evaluate the relationship between indoor and outdoor PM levels. PM1.0, PM2.5, and PM10 concentrations were measured over a 3-month period outside each hospital with parallel sampling at four indoor locations in patient wards. The results indicated that mean indoor concentrations at the sampling sites (PM1.0=17.8g/m(3), PM2.5=45.5g/m(3), and PM10=162.7g/m(3)) were found to be lower than outdoors levels (PM1.0=20.6g/m(3), PM2.5=62.1g/m(3), and PM10=300.6g/m(3)). Outdoor and indoor PM mass concentrations were associated with PM1.0, PM2.5, and PM10.0. Ambient wind speed also influenced the indoor/outdoor relationship for PM1.0 and PM2.5 but not for PM10. The average I/O ratios for PM2.5 in the intensive care unit (ICU) and children's ward at Shahid Beheshti Hospital were close to or above 1.00. Indoor PM1.0 and PM2.5 concentrations were found to be positively associated with outdoor PM1.0 and PM2.5 concentrations, but no relationship was observed with PM10. The present findings may inform policymakers in implementing evidence-based efforts for the aim of improving the indoor air quality in closed and confined spaces.
Keywords: Indoor air quality; PM2; 5; PM10; Hospitals; Iran; LOWER RESPIRATORY-INFECTIONS; PARTICULATE MATTER; PM2.5; PARTICLES; WINTER; Environmental Sciences & Ecology